2021
DOI: 10.1038/s41598-021-92407-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the viscosity of volcanic melts from the vibrational properties of their parental glasses

Abstract: The numerical modelling of magma transport and volcanic eruptions requires accurate knowledge of the viscosity of magmatic liquids as a function of temperature and melt composition. However, there is growing evidence that volcanic melts can be prone to nanoscale modification and crystallization before and during viscosity measurements. This challenges the possibility of being able to quantify the crystal-free melt phase contribution to the measured viscosity. In an effort to establish an alternative route to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 82 publications
(155 reference statements)
3
26
0
Order By: Relevance
“…2). We therefore used T g and m derived elsewhere by calorimetry and Brillouin spectroscopy 36 . Literature data enabled the very accurate description of high-temperature concentric-cylinder data (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). We therefore used T g and m derived elsewhere by calorimetry and Brillouin spectroscopy 36 . Literature data enabled the very accurate description of high-temperature concentric-cylinder data (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We attribute this difference to small but significant differences in total iron and titanium content, which can dramatically affect the tendency of the magmas to reach oversaturation in the vicinity of T g and (nano)crystallize. We thereby emphasize the need for a critical review and validation of the published viscosity data, providing a vademecum for correct experimental determination of viscosity based on our previous studies 32,36 .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…[33] Recently, it has been demonstrated that the BP position and the ratio of the bulk and shear moduli of volcanic and technical glasses correlate firstly with their parental melt fragility and secondly with the system chemistry, thus allowing an accurate estimation of the melt viscosity. [35] Here, we present a thorough characterization of four synthetic anhydrous basaltic glasses, showing the effect of Na-K mixing on their glass transition temperatures (T g ), resulting structures and the dynamical properties such as the BP. The composition of our samples mimics the overall percentage distribution of the chemical constituents of basalts on Earth [36] and explores a M a range (4.1 ≤ M a ≤ 4.8), which has identified optimal for CBFs manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Recently, it has been demonstrated that the BP position and the ratio of the bulk and shear moduli of volcanic and technical glasses correlate firstly with their parental melt fragility and secondly with the system chemistry, thus allowing an accurate estimation of the melt viscosity. [ 35 ]…”
Section: Introductionmentioning
confidence: 99%